A novel double-perovskite Gd2ZnTiO6:Mn4+ red phosphor for UV-based w-LEDs: structure and luminescence properties. Issue 12 (10th March 2016) - Chen, Hui; Lin, Hang; Huang, Qingming; Huang, Feng; Xu, Ju; Wang, Bo; Lin, Zebin; Zhou, Jiangcong; Wang, Yuansheng
Abstract : This work highlights a novel double-perovskite red phosphor Gd2 ZnTiO6 :Mn 4+ for UV-based warm white LEDs. Abstract : Red-emitting Mn 4+ activated oxide phosphors with a cheap price and excellent physical/chemical stability have become a hot research topic for their potential applications in white LEDs (w-LEDs). Herein, we report a novel double-perovskite Gd2 ZnTiO6 :Mn 4+ (GZT:Mn 4+ ) red phosphor. The material microstructures were characterized with the aid of XRD Rietveld refinement and HRTEM observations. The luminescence properties and dynamics of Mn 4+ in GZT were studied in detail using low/room temperature steady/transient spectroscopic techniques. The crystal field strength and nephelauxetic effect influencing the Mn 4+ emission energy were also analyzed. It is revealed that the special crystal structure of GZT featuring alternately slant-wise arranged [TiO6 ]/[ZnO6 ] octahedrons with the [–Mn 4+ –O 2− –Zn 2+ –] bond angle deviating from 180° is beneficial to achieving efficient Mn 4+ : 2 Eg → 4 A2 transition in the deep-red region. After mixing the red-emitting GZT:Mn 4+ with the commercial blue and green phosphors in various ratios, and then coupling the mixture with a 365 nm UV chip to build a w-LED, the white light was found to evolve from cool to warm with a tunable correlated color temperature (CCT) from 6977 K to 4742 K, a color rendering index (CRI) up to 82.9, and an improved R 9 value to 43, which validates that GZT:Mn 4+ is a promising red color converter for UV-based w-LEDs.